2016
DOI: 10.1038/onc.2016.459
|View full text |Cite
|
Sign up to set email alerts
|

ER stress protein AGR2 precedes and is involved in the regulation of pancreatic cancer initiation

Abstract: The mechanisms of initiation of pancreatic ductal adenocarcinoma (PDAC) are still largely unknown. In the present study, we analysed the role of anterior gradient-2 (AGR2) in the earliest stages of pancreatic neoplasia. Immunohistochemical analysis of chronic pancreatitis (CP) and peritumoral areas in PDAC tissues showed that AGR2 was present in tubular complexes (TC) and early pancreatic intraepithelial neoplasia (PanINs). Moreover, AGR2 was also found in discrete subpopulations of non-transformed cells neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 46 publications
7
71
0
Order By: Relevance
“…In pancreatic cancer, it has been reported that AGR2 up‐regulates during inflammatory phase of pancreatic ductal adenocarcinoma (PDAC) development [Dumartin et al., ] and that ER stress induced by AGR2 is associated with the acquisition of a pro‐inflammatory phenotype. Furthermore, ER stress could be the mediator of an intercellular communication between epithelial and stromal cells [Dumartin et al., ].…”
Section: Agr2 and The Tnsmentioning
confidence: 99%
See 2 more Smart Citations
“…In pancreatic cancer, it has been reported that AGR2 up‐regulates during inflammatory phase of pancreatic ductal adenocarcinoma (PDAC) development [Dumartin et al., ] and that ER stress induced by AGR2 is associated with the acquisition of a pro‐inflammatory phenotype. Furthermore, ER stress could be the mediator of an intercellular communication between epithelial and stromal cells [Dumartin et al., ].…”
Section: Agr2 and The Tnsmentioning
confidence: 99%
“…In pancreatic cancer, it has been reported that AGR2 up‐regulates during inflammatory phase of pancreatic ductal adenocarcinoma (PDAC) development [Dumartin et al., ] and that ER stress induced by AGR2 is associated with the acquisition of a pro‐inflammatory phenotype. Furthermore, ER stress could be the mediator of an intercellular communication between epithelial and stromal cells [Dumartin et al., ]. It is possible that paracrine mediators, including inflammatory mediators such as reactive oxygen species, are involved in the intercellular communication between ER stress and AGR2 expression; however, this hypothesis remains to be addressed further.…”
Section: Agr2 and The Tnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, once activated, the pro-survival XBP1 was noted to be activated for a longer time period in cancer cells when compared to normal cells[39]. As well as adapting to chronic ER stress, it has been recently postulated that anterior-gradient 2 (AGR2) may contribute to the initiation and development of PDAC[40]. As AGR2 is a gene associated with protein folding and maturation which is expressed in pancreatic cells under ER stress conditions, it may become a key piece in our understanding of how PDACs arise, as well as a potential future therapeutic target.…”
Section: Cancer Therapy and Er Stressmentioning
confidence: 99%
“…Disruption of autophagy via genetic deletion of its key mediator autophagy related 5 (ATG5) in mice led to increased levels of reactive oxygen species, augmented endoplasmic reticulum (ER) stress, and development of spontaneous chronic atrophic pancreatitis [79]. Conceivably, autophagy appears to limit ER stress and pro-tumorigenic mediators, and protect during incipient pancreatic oncogenesis [80, 81]. …”
Section: Additional Local and Systemic Imbalancesmentioning
confidence: 99%